Classification and Control Strategies for Malaria, Plague, and Tuberculosis: Klasifikasi dan Strategi Pengendalian Malaria, Wabah, dan Tuberkulosis - Wisam Hasan Hadi; Mustafa Abdul kareem Mustaf; Ammar Abdulwahid Jbarah AL-Karawi; Shifaa Waleed Khaled (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Infectious diseases continue to pose a significant global health challenge, with malaria, plague, and tuberculosis contributing to high morbidity and mortality rates. Globalization has further accelerated their spread across borders. Specific Background: Despite medical advancements, these diseases persist due to factors such as drug resistance, high transmission rates, and regional endemicity. Pulmonary tuberculosis, in particular, remains a major concern due to its chronic nature and multidrug resistance. Knowledge Gap: Comparative studies classifying these diseases based on severity, epidemiological impact, and treatment response remain limited, making it difficult to prioritize intervention strategies effectively. Aims: This study classifies malaria, plague, and pulmonary tuberculosis using global health data to assess their epidemiological burden and treatment response. Results: Pulmonary tuberculosis presents the greatest long-term threat due to its resistance patterns. Plague, while acutely lethal, is highly treatable with timely antibiotics. Malaria remains a significant burden but is manageable with appropriate interventions. Novelty: This study integrates statistical analyses of mortality rates, transmission dynamics, and drug resistance patterns to provide a comparative classification of these diseases. Implications: Findings emphasize the necessity of early diagnosis, targeted drug development, and strengthened surveillance to enhance global infectious disease control efforts. Highlights: Infectious diseases remain a global challenge due to transmission and drug resistance. Tuberculosis is persistent, plague is acutely lethal, malaria burdens endemic regions. Targeted interventions, early diagnosis, and drug development are crucial for control. Keywords : Malaria, plague, tuberculosis, epidemiology, response to treatment and burden of disease